Rights-based fisheries governance: from fishing rights to human rights - Allison, Edward H.; Ratner, Blake D.; Åsgård, Björn; Willmann, Rolf; Pomeroy, Robert S.; Kurien, John (Wiley, 2012)
In the last twenty years, policy prescriptions for addressing the global crisis in fisheries have centred on strengthening fisheries governance through clarifying exclusive individual or community rights of access to fishery resources. With a focus on small‐scale developing‐country fisheries in particular, we argue that basing the case for fishery governance reform on assumed economic incentives for resource stewardship is insufficient when there are other sources of insecurity in people’s lives that are unrelated to the state of fishery resources. We argue that more secure, less vulnerable fishers make more effective and motivated fishery managers in the context of participatory or rights‐based fisheries governance, and we further suggest that insecurity among fishers living in poverty can be most effectively addressed by social and political development that invokes the existing legal framework supporting the Universal Declaration of Human Rights. This perspective goes well beyond the widely advocated notion of ‘rights‐based fishing’ and aligns what fishery sector analysts call the ‘rights‐based approach’ with the same terminology used in the context of international development. Embedding the fisheries governance challenge within a broader perspective of human rights enhances the chances of achieving both human development and resource sustainability outcomes in small‐scale fisheries of developing countries.